Artificial Intelligence and its Impact on the Quality of English Language Teaching: An Applied Study on English Language Teachers in Primary Schools - Asir Region - Alahmari, Aliah Mohammed (Journal of Educational and Psychological Sciences, 2025)
The study aimed to explore artificial intelligence (AI) and its impact on the quality of English language teaching in primary schools. The research employed the descriptive-analytical method and the correlational approach by utilizing path analysis techniques to investigate the effect of AI technologies on improving the quality of English language education. A questionnaire consisting of 35 items was designed and distributed electronically via Telegram to English language teachers in primary schools in the Asir region. The study sample included 236 responses. The results indicated that there is a statistically significant effect of AI technologies on improving the quality of English language education, particularly with smart content technologies, at a significance level of (0.000<0.05) (***). Additionally, there is a statistically significant effect of AI technologies on enhancing the quality of English language teaching through virtual reality technologies at a significance level of (0.03<0.05). Furthermore, a statistically significant effect was found for smart learning technologies on improving English language teaching quality at a significance level of (0.039<0.05). However, no statistically significant effect was found for augmented reality (AR) technologies, with significance levels (>0.05), nor for Layer technologies, with significance levels of (0.073>0.05). The study recommended intensifying the use of AI technologies in English language teaching and conducting further research to identify the main obstacles to implementing AI technologies in improving and developing the quality of English language education in Saudi universities.